Cellulose-Based Solid Electrolyte Membranes Through Microwave Assisted Regeneration and Application in Electrochromic Displays - Duarte, Paulo; Pereira, Sónia; Cunha, Inês; Pimentel, Ana; Dionísio, Madalena; Fortunato, Elvira; Martins, Rodrigo; Pereira, Luís (Frontiers in Materials, 2020)
One of the most current trends in applied electrochemistry is the development of solid ionic conductors with electrical, mechanical and optical properties tailored for a specific functional application. Moreover, particular interest exists in materials with low environmental impact and low cost where matters as sustainability and recyclability are considered. In this study, these concerns were considered by developing a solid-state electrolyte based on regenerated cellulose that meets the requirements for application in electrochromic devices. This soft-matter electrolyte exhibits particularly high room temperature ionic conductivity in the range of 6.5 mS cm-1 and Young’s Modulus in the range 3.7 GPa. Optimized electrolyte membranes were applied to inorganic optically active films resulting in all-solid-state electrochromic devices with performances reaching a practical level, retaining its optical modulation characteristics after hundreds of cycles.